Pediatric Tracheostomy: 10-year-experience in a Tertiary Center - Paupério, Anita (2021)
Objective: to evaluate pediatric patients with tracheostomy in our tertiary center, regarding demographic data, indications, comorbidities, complications and rates of decannulation. Material and Methods: Retrospective study of all patients under the age of 18 who underwent tracheostomy by the Otorhinolaryngology Service at Hospital Garcia de Orta, between January 2010 and December 2019. Results: 15 patients were identified and studied. The procedure was elective in all cases. The most frequent indications for tracheostomy were laryngomalacia (33,3%) and prolonged mechanical ventilation (26,7%). No intraoperative complications were recorded. By the end of this study, 7 children (46,7%) were successfully decannulated. Conclusions The statistical analysis of our study is in line with the data in the current literature. The technical aspects and surgical indications for pediatric tracheostomy have specific characteristics, therefore highly differentiated treatment and a multidisciplinary approach is crucial for these patients.